A Budget Proposal for China's Public Long-Term Care Policy. Issue 1 (1st January 2017) - Lu, Bei; Liu, Xiaoting; Yang, Mingxu
ABSTRACT: Long-term care (LTC) policy is at an experimental stage in China, characterized by various regional pilot programs. The public cost of LTC is difficult to estimate due to a lack of clarity about policy detail from the central government. This article analyzes the current disabled status for vulnerable older people without sufficient financial resources and family supports. It focuses on estimating a safety net public subsidy policy for LTC services in China, both for today and into the future, using China Health and Retirement Longitudinal Survey (CHARLS) data, 2011 wave, with the methods of multinomial logistic regression and simulation. The key contribution is to estimate the future disability trend and LTC public cost based on changes in education, population ageing, and urbanization. Disability prevalence might be decreasing partly due to higher education, urbanization, and better health care, and the overall public LTC costs might be growing by the results of projection.